Binary System of Cyclohexane with Chloroalkanes, Benzene, Toluene and Xylene - N. Modi, Ashvin; Patel, Dinesh; Desai, C.M. (Asian Journal of Chemistry, 2010)
Dye indicator spectral absorbance of binary mixtures ofcyclohexane with chloroalkanes, benzene, toluene and xylene indicatemolecular interactions (high or low) among these liquids onthe graphs showing them.